Aspectos ecológicos e sócio-econômicos da pesca profissional no reservatório da UHE de Ilha Solteira, município de Rubinéia-SP - Angeluci, Carlos Henrique Gonçalves (2004)
ZThe, Scoln "str1uct9ion7 o0f jlanrge rehsypdornoseel ettroi cn aptliaonntasl idn emBraanzdil , fohra se nsehrogwy.n Tah ocsoen sciodenr^abclue oinnc rmeaasdee, possible the suraing of environment with charactenstics that are considered to be between nvers and labes Besidesftat they created a new landscape making possible ,t utd.sation for multiple uses The impoundment of large rivers can be considered the first impact on these areas, affecting directly the iehthyofauna by redution of its biod.yers.ty, and also m many cases can have influence on decrease of fishing productivity. Weekly notes were gotten from arnval fishing, in Ilha Solteira reservoir in Rubineia municipal district, with the object to eyalnatethe socal-economical conditions of professional fishers in the region, and also the ecological aspects of fishing m die area There has been found a sntall number of spec.es, present at arnval, totahng g n tne area Orders. The lake in study presents a commumty that has e number of 21, re ei. ° reSult there has been a jow variety of species and a been subm.tted to contoons “f strees as the XPreí™Tb“rfoorX of 64.329 Kg. Of this amount, 45% refer to the Geophagus 2 until Octobe - , pjagioscion squamosissimus kind, the second that had the surmamensts^, and 27/o to tne Q swinamensis largest contnbuUon in the bornas capm Coefficient of Variation during the period of e one that presented e mainly on the use of gill nets. The reservoir presents a s udy. Jhe fishing in t e a sauare Km, and lower productivity with values of fishing close to^SK Th ^n/dT The fisherman in their majority have a very low degree of education, 15 Kg/fisherman/dc y. . • t soive their problems, and a lack of information regarding also a lack of political orgamzation to soive h ° the aspects of preservation of natural resources.